Aquaporin‐1 inhibition reduces metastatic formation in a mouse model of melanoma. Issue 2 (17th October 2017) - Simone, Laura; Gargano, Concetta Domenica; Pisani, Francesco; Cibelli, Antonio; Mola, Maria Grazia; Frigeri, Antonio; Svelto, Maria; Nicchia, Grazia Paola
Abstract: Aquaporin‐1 (AQP1) is a proangiogenic water channel protein promoting endothelial cell migration. We previously reported that AQP1 silencing by RNA interference reduces angiogenesis‐dependent primary tumour growth in a mouse model of melanoma. In this study, we tested the hypothesis that AQP1 inhibition also affects animal survival and lung nodule formation. Melanoma was induced by injecting B16F10 cells into the back of C57BL6J mice. Intratumoural injection of AQP1 siRNA and CTRL siRNA was performed 10 days after tumour cell implantation. Lung nodule formation was analysed after the death of the mice. Western blot was used to quantify HIF‐1α, caspase‐3 (CASP3) and metalloproteinase‐2 (MMP2) protein levels. We found that AQP1 knock‐down (KD) strongly inhibited metastatic lung nodule formation. Moreover, AQP1 siRNA‐treated mice showed a twofold survival advantage compared to mice receiving CTRL siRNAs. The reduced AQP1‐dependent tumour angiogenesis caused a hypoxic condition, evaluated by HIF‐1α significant increase, in turn causing an increased level of apoptosis in AQP1 KD tumours, assessed by CASP3 quantification and DNA fragmentation. Importantly, a decreased level of MMP2 after AQP1 KD indicated a decreased activity against extracellular matrix associated with reduced vascularization and metastatic formation. In conclusion, these findings highlight an additional role for AQP1 as an important determinant of tumour dissemination by facilitating tumour cell extravasation and metastatic formation. This study adds knowledge on the role played by AQP1 in tumour biology and supports the view of AQP1 as a potential drug target for cancer therapy.